The Impact of Parasitic Infestation on Nutritional Status and Micronutrients among Children - Usama M. Alkholy; Sherief M. El Gebaly; Walaa E. M. A. Morsi; Waleed E. Elawamy; Samia E. Etewa; Asmaa M. Yousef (Journal of Parasitology Research)
Background. Micronutrient deficiency is a great problem that is augmented by infection and poor nutrition. Iron, zinc, and selenium are trace elements needed for human growth. Objective. To investigate the impact of parasitic infection on nutritional status and serum iron, zinc, and selenium in children attending Pediatrics Outpatient Clinic of Zagazig University Hospitals. Subjects and Methods. A case-control study included 140 parasitic infected children and one hundred age- and sex-matched controls. Anthropometric measures were evaluated using specific Egyptian growth charts. Parasites were detected in stool specimens using standard microscopic methods. Atomic absorption spectrophotometer was used for the detection of serum iron, zinc, and selenium. To examine the statistical relationship between intestinal parasitic infection and the relevant variables (gender, residence, socioeconomic status, and age group), the nonparametric chi-square (χ2) test was used. Data were analyzed statistically using SPSS version 25. Results. Parasitic infected children showed a statistically significant low weight for age, height for age, and BMI. Serum iron, zinc, and selenium were significantly lower in parasitic infected children than controls. Serum iron, zinc, and selenium have significant positive correlations with weight, height, and BMI, respectively. Conclusion. Studied serum micronutrients especially zinc and iron and anthropometric indices were significantly lower in parasitically infected children.